Sero-epidemiological survey and risk factors associated with bovine brucellosis among slaughtered cattle in Nigeria. (2016)
Bovine brucellosis is endemic in Nigeria; however, limited data exist on nationwide studies and risk factors associated with the disease. Using a cross-sectional sero-epidemiological survey, we determined the prevalence of and risk factors for brucellosis in slaughtered cattle in three geographical regions of Nigeria. Serum samples from randomly selected unvaccinated cattle slaughtered over a period of 3 years (between December 2010 and September 2013) from northern, southern and south-western Nigeria were tested for antibodies to Brucella abortus using the Rose Bengal test. Data associated with risk factors of brucellosis were analysed by Stata Version 12. In all, 8105 cattle were screened. An overall seroprevalence of 3.9% (315/8105) was recorded by the Rose Bengal test, with 3.8%, 3.4% and 4.0% from the northern, southern and south-western regions, respectively. Bivariate analysis showed that cattle screened in northern Nigeria were less likely to be seropositive for antibodies to Brucella spp. than those from south-western Nigeria (odds ratio = 0.94; 95% confidence interval: 0.73–1.22). However, logistic regression analysis revealed that breed ( p = 0.04) and sex ( p £ 0.0001) of cattle were statistically significant for seropositivity to Brucella spp. The study found that brucellosis was endemic at a low prevalence among slaughtered cattle in Nigeria, with sex and breed of cattle being significant risk factors. Considering the public health implications of brucellosis, we advocate coordinated surveillance for the disease among diverse cattle populations in Nigeria, as is carried out in most developed countries.